2009
DOI: 10.1002/biof.29
|View full text |Cite
|
Sign up to set email alerts
|

Physiological factors that regulate skin pigmentation

Abstract: More than 150 genes have been identified that affect skin color either directly or indirectly, and we review current understanding of physiological factors that regulate skin pigmentation. We focus on melanosome biogenesis, transport and transfer, melanogenic regulators in melanocytes and factors derived from keratinocytes, fibroblasts, endothelial cells, hormones, inflammatory cells and nerves. Enzymatic components of melanosomes include tyrosinase, tyrosinase-related protein 1 and dopachrome tautomerase, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
410
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(439 citation statements)
references
References 58 publications
4
410
0
12
Order By: Relevance
“…Melanogenesis has been the interest of intense research for many decades. Melanocytes are unique cells that produce melanosomes, specific melanin-containing intracellular organelles [45]. In our study, the effect of lomefloxacin on melanocytes viability was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Melanogenesis has been the interest of intense research for many decades. Melanocytes are unique cells that produce melanosomes, specific melanin-containing intracellular organelles [45]. In our study, the effect of lomefloxacin on melanocytes viability was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…We found that gd TCR + intraepithelial lymphocytes were reduced by 50% in AhR-KO mice, but frequencies of gd T cells in blood or spleen did not differ between AhR genotypes (Supplemental Data 3D, 3E). It is known that the ligand of c-Kit, stem cell factor (SCF), is secreted by epidermal cells (38). We therefore hypothesized that SCF/c-Kit signaling might be affected by AhR deficiency.…”
Section: C-kit Expression Is Ahr Dependentmentioning
confidence: 99%
“…It has been reported that skin pigmentation is regulated by a variety of intrinsic and extrinsic factors [7,8] , as well as diverse signaling pathways including protein kinase A (PKA), phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinases (MAPKs) [9][10][11][12][13] . In particular, the MAPK kinase (MEK)/extracellular signal-regulated kinase (ERK) and the PI3K/Akt pathways have been shown to negatively regulate melanin synthesis in melanocytes and melanoma cells [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%